Antitrypanosomal therapy for Chagas disease: A single center experience with adverse drug reactions and strategies for enhancing treatment completion. - Katherine Reifler; Alyse Wheelock; Samantha M Hall; Madolyn Dauphinais; Samuel Roytburd; Michael Maiullari; Alejandra Salazar; Ashley Maldonado; Helen Mahoney West; Julia R Köhler; Elizabeth D Barnett; Deepa M Gopal; et al. (PLoS Neglected Tropical Diseases)
Anti-trypanosomal therapy is generally recommended for individuals under age 50 with the indeterminate form of Chagas disease to prevent disease progression. However, benznidazole and nifurtimox are associated with adverse drug reactions. We performed a retrospective review of treatment tolerability among patients with Chagas disease referred to Boston Medical Center from June 2016 to June 2024. There were 125 individuals evaluated, of whom 32 (25.6%) had contraindications to and 2 (1.6%) declined antiparasitic treatment. Ninety-one started therapy (83 with benznidazole, 8 with nifurtimox) with monitoring co-managed by infectious diseases physicians and pharmacists. Following benznidazole initiation, 70 (84.3%) had at least one adverse event, of which allergic (39/83, 47.0%), gastrointestinal (38/83, 45.8%), and neuropsychiatric (33/83, 39.8%) reactions were most common. Rash led to treatment discontinuation in 19 patients (22.9%) and met criteria for grade 3 severity in 13 (15.7%). Adjunctive therapies for rash included topical and systemic steroids and systemic antihistamines. Peripheral neuropathy led to treatment cessation for 13 patients (15.7%). Gastrointestinal adverse effects occurred in 38 patients (45.8%), were relatively mild, and managed with H2 blockers or proton pump inhibitors. Thirty (36.1%) patients were unable to complete 60 days of benznidazole, of whom 15 switched to nifurtimox. Eight patients started with nifurtimox during a benznidazole shortage. Nifurtimox was more frequently associated with gastrointestinal side effects (21/23, 91.3%) compared to benznidazole. Ultimately, 83 patients (91.2%) received at least 30 days, and 68 patients (74.7%) completed at least 60 days of benznidazole or nifurtimox. Multiple strategies were used to prevent and alleviate adverse events; multi-disciplinary team management was essential. These findings underscore the support needed for individuals with Chagas disease to tolerate and complete therapy and highlight the need for safer and more effective options to facilitate access to treatment.